Strengthening Clinical Skills Using Peer-Student Validation. Issue 5 (September 2015) - O'Brien, Tara; Talbot, Laura; Santevecchi, Eileen
Abstract : This study compared nursing students' satisfaction with the peer-student validation (PSV) method for learning basic skills and the traditional method. Students in the PSV group (n = 41) were compared with students in the traditional method group (n = 46) using a posttest survey. The PSV group reported significantly greater improvements in communication with their patients ( P < .04) and time to practice skills ( P < .01) and were more satisfied with the organization of the skills laboratory content ( P < .04) than the traditional group.